2006
DOI: 10.1088/0957-4484/18/4/044030
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the speed limit with atomic force microscopy

Abstract: High-speed atomic force microscopy (AFM) is important for following processes that occur on sub-second timescales for studies both in biology and materials science, and also for the ability to examine large areas of a specimen at high resolution in a practical length of time. Further developments of the previously reported high-speed contact-mode AFM are described. Two instruments are presented: (i) a high-speed flexure stage arrangement capable of imaging at a video rate of 30 fps, and (ii) an ultra-high spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
148
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(150 citation statements)
references
References 14 publications
0
148
0
1
Order By: Relevance
“…Imaging rate, 1.03 fps (×20 playback); scan size, 800 × 800 nm 2 [98]. ・Crystallization of a CaCO 3 thin film from supersaturated solution [72] ・Ultrafast imaging of collagen [58] ・Brownian motion & photo-degradation of π-conjugated polyrotaxane [73] ・DNA translocation and looping by type III restriction enzyme [74] ・Biotinylated DNA-streptavidin interaction [75] Miles Miles Shinohara Takeyasu Trimitsu 2008 5 ・Anisotropic diffusion of point defects in streptavidin 2D crystals [76] ・Identification of intrinsically disordered regions of proteins [77] ・Human chromosomes in liquid [78] ・DNA-nuclease interaction [ ・Dynamic equilibrium at the edge of bR 2D crystals [81] ・Structural change of CaM and actin polymerization on streptavidin 2D crystals [82] ・Unidirectional translocation of cellulase along cellulose fibers [83] ・Translocation of EcoRII restriction enzyme along DNA [84] ・Fabrication and imaging of hard material surface [85] ・Purple membrane in contact-mode HS-AFM [86] ・Thermal motion of π-conjugated polymer chain [87] ・Opening of 3D hollow structure of DNA Origami [88] ・Opening of 3D hollow structure of DNA Origami [89] ・ATP-induced conformational change in P2X 4 ・Walking myosin V along an actin filament [91] ・Photo-induced structural change in bR [92] ・2D crystal formation of annexin A-V and height change of p97 [93] ・Analysis of components covering magnesotome surface [94] ・Time course of cell death by antimicrobial peptide [95] ・Dissolution of extreme UV exposed resist films under developing [96] ・Dissolution of extreme UV exposed resist films under developing [97] ・Process of forming supported planar lipid bilayer [98] ・Self assembly of amyloid-like fibrils [99] ・Effect of ClpX on FtsZ polymerization ...…”
Section: Resultsmentioning
confidence: 99%
“…Imaging rate, 1.03 fps (×20 playback); scan size, 800 × 800 nm 2 [98]. ・Crystallization of a CaCO 3 thin film from supersaturated solution [72] ・Ultrafast imaging of collagen [58] ・Brownian motion & photo-degradation of π-conjugated polyrotaxane [73] ・DNA translocation and looping by type III restriction enzyme [74] ・Biotinylated DNA-streptavidin interaction [75] Miles Miles Shinohara Takeyasu Trimitsu 2008 5 ・Anisotropic diffusion of point defects in streptavidin 2D crystals [76] ・Identification of intrinsically disordered regions of proteins [77] ・Human chromosomes in liquid [78] ・DNA-nuclease interaction [ ・Dynamic equilibrium at the edge of bR 2D crystals [81] ・Structural change of CaM and actin polymerization on streptavidin 2D crystals [82] ・Unidirectional translocation of cellulase along cellulose fibers [83] ・Translocation of EcoRII restriction enzyme along DNA [84] ・Fabrication and imaging of hard material surface [85] ・Purple membrane in contact-mode HS-AFM [86] ・Thermal motion of π-conjugated polymer chain [87] ・Opening of 3D hollow structure of DNA Origami [88] ・Opening of 3D hollow structure of DNA Origami [89] ・ATP-induced conformational change in P2X 4 ・Walking myosin V along an actin filament [91] ・Photo-induced structural change in bR [92] ・2D crystal formation of annexin A-V and height change of p97 [93] ・Analysis of components covering magnesotome surface [94] ・Time course of cell death by antimicrobial peptide [95] ・Dissolution of extreme UV exposed resist films under developing [96] ・Dissolution of extreme UV exposed resist films under developing [97] ・Process of forming supported planar lipid bilayer [98] ・Self assembly of amyloid-like fibrils [99] ・Effect of ClpX on FtsZ polymerization ...…”
Section: Resultsmentioning
confidence: 99%
“…19,25,26 Furthermore, the scanning speed is limited and does not exceed speeds much higher than ϳ1 − 2 Hz, which does not permit time-dependent measurements on short time scales--a particular problem for biophysical SPM studies. 7,27 The imaging of nanoclusters with high resolution and high scanning speeds is clearly missing and is of high interest not only in nanocatalysis but also in any area of surface science and nanotechnology. Recently, we have qualitatively shown that the lateral size and shape of nanoclusters can be more accurately imaged with high scanning speeds if the so-called constant height mode in dynamic SFM is used.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence video microscopy can be performed at faster imaging rates, using bright fluorescent labels and faster video cameras. The imaging rate of AFM can be enhanced to 1 ms/frame [28]. This is accomplished by discarding the tapping-mode operation and the feedback control for maintaining a constant tip-sample interaction force.…”
Section: Time Resolutionmentioning
confidence: 99%